Anthocyanin Retention of Cranberry (Vaccinium macrocarpon) Juice Subjected to Different Nanofiltration Conditions - Kong Ah-Hen; Marcia Costa; Susan Poo; Roberto Lemus-Mondaca (Journal of Chemistry)
The aim of this work was to evaluate the retention of anthocyanin during a nanofiltration process of cranberry juice. Nanofiltration membranes, HC-50P DDS with an effective area of 0.36 m2 in a plate/frame nanofilter system, DDS Lab Module, were used for the experiments. Juice feed flow rate varied from 1.0 to 12.0 L min−1 at transmembrane pressures between 20 and 40 bar (2026 and 4052 kPa). Permeate flux reached a maximum value of 41.3 L h−1 m−2 at a pressure of 40 bar and a feed rate of 12 L min−1, showing a direct dependency on these two parameters. Retention coefficients of anthocyanin of 0.94 to 0.99 corresponding to percentage recovery between 93 and 99% were obtained. Total anthocyanin content increased to values between 237 and 287 mg L−1 from original concentration of 82 to 97 mg L−1 in feed solution. Total soluble solids were also retained on the nanofilter. Both anthocyanin retentate and permeate obtained by nanofiltration could be potential functional ingredients for the food and nutraceutical industry.